Case Report: Lethal mitochondrial cardiomyopathy linked to a compound heterozygous variant of PARS2 - Jing, Siyuan; Yao, Qiuyan; Wu, Mei; Li, Yifei (Frontiers in Cardiovascular Medicine, 2024)
Introduction Variants in the PARS2 gene have been previously associated with developmental and epileptic encephalopathy. PARS2 deficiency was characterized as neurodevelopmental and neurodegenerative disorders with early-onset seizures and global developmental delay. Herein, we reported the first case with severe heart failure due to lethal mitochondrial cardiomyopathy with PARS2 compound heterozygous variants. Case presentation This patient demonstrated fatigue, chest tightness, and shortness of breath. An acute major illness had been identified at initial evaluation, which was characterized by severe diaphoresis, dizziness, and fatigue. Blood–urine tandem mass spectrometry found multiple disorders in acid metabolism, characterized as increased homovanillic acid (130.39 mmol/L) and 2-hydroxyisovaleric acid (1.70 mmol/L), which are associated with myocardial injuries. Therefore, an inherited metabolic disorder had been suspected and whole-exome sequencing performed, revealing a novel compound heterozygous variant of c.953C>T and c.283G>A on PARS2. Echocardiography confirmed the findings from MRI, which presented an increased left ventricular diameter at the end of the diastolic stage. The molecular structure of SYPM had been established as AF-Q7L3T8-F1, and the identified mutant sites located in the proline-tRNA ligase domain. However, the patient died due to severe heart failure. Conclusion This is the first case to reveal a novel compound heterozygous variant of PARS2-induced lethal cardiomyopathy with unreversed heart failure. Thus, this report enhances our understanding of mitochondrial tRNA function in maintaining heart function.